Wafer-scale synthesis of monolayer two-dimensional porphyrin polymers for hybrid superlattices - Zhong, Yu; Cheng, Baorui; Park, Chibeom; Ray, Ariana; Brown, Sarah; Mujid, Fauzia; Lee, Jae Ung; Zhou, Hua; Suh, Joonki; Lee, Kan Heng; Mannix, Andrew J.; Kang, Kibum; et al. (Science, 2019)
The large-scale synthesis of high-quality thin films with extensive tunability derived from molecular building blocks will advance the development of artificial solids with designed functionalities. We report the synthesis of two-dimensional (2D) porphyrin polymer films with wafer-scale homogeneity in the ultimate limit of monolayer thickness by growing films at a sharp pentane/water interface, which allows the fabrication of their hybrid superlattices. Laminar assembly polymerization of porphyrin monomers could form monolayers of metal-organic frameworks with Cu2+ linkers or covalent organic frameworks with terephthalaldehyde linkers. Both the lattice structures and optical properties of these 2D films were directly controlled by the molecular monomers and polymerization chemistries. The 2D polymers were used to fabricate arrays of hybrid superlattices with molybdenum disulfide that could be used in electrical capacitors.